Relações externas congolesas na primeira década do séc. XVII, em termos de D. Álvaro II: a emabixada de D. Garcia Baptista e D. António Manuel - Amaral, Ílidio (Finisterra, 1997)
FOREIGN CONGOLESE RELATIONS IN THE FIRST DECADE OF THE XVIIth CENTURY, IN THE TIMES OF D. ALVARO II: THE EMBASSY OF D. GARIA BAPTISTA AND D. ANTONIO MANUEL - This article provides an insight into the diplomatic relationship between the Kingdom of Congo, Portugal and Spain and the Vatican in the first decade of the XVIIth century (1604-1608), being king of Congo D. Alvaro II, whose african name was Mpangu-a-Nimi Lukeni Lua Mvemba, and reigned from 1587 to 1618. Some notes are given through several examples of congolese embassies, one of them being composed by D. Garcia Baptista, charged of the affairs more closely related to the Philipine administration (D. Filipe II), and D. Antonio Manuel, the marquis of Vunta, whose destination was the Vatican, to meet the Pope. Both arrived in Portugal in the last quarter of 1605, after a long and troubled journey with a halt in Brazil. The fist one brought a long memorial that was submitted to a minute appreciation by the Council of India and by the viceroy of Portugal. Later he went back to Congo. The second met with the greatest difficulties on his voyage to Rome where he arrived very ill, on January the 3rd 1608 and died on the 5th, after transmitting to the Pope the essencial of his mission. He was entitled to a magnificent funeral and was buried in the church of Santa Maria Maior, where his tomb still exists as well as a bust in marble attributed to the school of Bernini. He was known among the romans as Nigrita